(untitled) (Journal of the College of Basic Education, 2025)
The importance of the study is represented in two aspects, the first of which is the theoretical importance. This study may contribute to identifying the reality of educational planning and crisis management in schools, and may provide a look at the obstacles to educational planning in crisis management. It may also help raise the level of educational planning and crisis management and develop it. As for the applied family, the results of senior leadership and department officials help. Education to evaluate and develop educational plans in schools. Training departments may also direct training courses to qualify school principals to build educational plans for crisis management. What is the reality of educational planning in neighboring crises from the point of view of school principals in the third Karkh Directorate? The problem of the study is formulated with the main question as follows: What is the reality of educational planning in crisis departments from the point of view of school principals in the third Karkh Education Directorate. The goal of the research is to prepare a measure of educational planning and crisis management for secondary school principals in the third Karkh Education Directorate. And the relationship between them. As for the research hypothesis, is there a correlation between educational planning and crisis management from the point of view of secondary school principals in the General Directorate of Education of Baghdad Al-Karkh Governorate III? As for the research methodology, the researcher used the descriptive approach with the survey method and correlational relationships. As for the research community and its samples, it was The research community was determined in an intentional manner, namely the principals of the girls’ secondary schools in the third Karkh district in Baghdad Governorate, who numbered (30) principals and were distributed among public and private schools in Baghdad Governorate. The research sample represented the entire research community, as the most important conclusions were that educational planning A major role in revealing the dangers of educational crises facing secondary school principals. The most important recommendations include paying attention to granting the necessary powers to school principals, which enables them to delegate some powers to school staff, which makes them have sufficient time for educational planning to manage crises.